Enantioselective Synthesis of 4-Silyl-1,2,3,4-tetrahydroquinolines via Copper(I) Hydride Catalyzed Asymmetric Hydrosilylation of 1,2-Dihydroquinolines - Xu-Xu, Qing-Feng; Yang, Pusu; Zhang, Xiao; You, Shu-Li (Synlett, 2021)
C–Si bonds were constructed by utilizing copper hydride-catalyzed asymmetric hydrosilylation of 1,2-dihydroquinolines, affording various chiral 4-silyl-1,2,3,4-tetrahydroquinolines in good yields and enantioselectivity. In addition, the C–Si bonds were transformed into C–O bonds with retention of stereochemistry through the Tamao oxidation, giving a series of useful 4-hydroxy-1,2,3,4-tetrahydroquinolines. This method with the enantioselective introduction of silyl groups provides an option to adjust bioactive properties of tetrahydroquinolines.
Keywords: 1,2-dihydroquinoline; 1,2,3,4-tetrahydroquinoline; copper hydride; asymmetric catalysis; hydrosilylation; dearomatization